Deep Brain Stimulation Does Not Modulate Auditory-Motor Integration of Speech in Parkinson's Disease - Bahners, Bahne H.; Florin, Esther; Rohrhuber, Julian; Krause, Holger; Hirschmann, Jan; van de Vijver, Ruben; Schnitzler, Alfons; Butz, Markus (Frontiers in Neurology, 2020)
Deep brain stimulation (DBS) has significant effects on motor symptoms in Parkinson’s disease (PD), but existing studies on the effect of DBS on speech are rather inconclusive. It is assumed that deficits in auditory-motor integration strongly contribute to Parkinsonian speech pathology. The aim of the present study was to assess whether subthalamic DBS can modulate these deficits. 20 PD patients (15 male, 5 female; 62.4 ± 6.7 years) with subthalamic DBS were exposed to pitch-shifted acoustic feedback during vowel vocalization and subsequent listening. Voice and brain activity were measured ON and OFF stimulation using magnetoencephalography (MEG). Vocal responses and auditory evoked responses time locked to the onset of pitch-shifted feedback were examined. A positive correlation between vocal response magnitude and pitch variability was observed for both, stimulation ON and OFF (ON: r = 0.722, p<0.001, OFF: r = 0.746, p<0.001). However, no differences of vocal responses to pitch-shifted feedback between the stimulation conditions were found (t(19)= - 0.245, p=0.809, d= - 0.055). P200m amplitudes of event related fields (ERF) of left and right auditory cortex (AC) and superior temporal gyrus (STG) were significantly larger during listening (left AC P200m: F(1,19)=10.241, p=0.005, f=0.734; right STG P200m: F(1,19)=8.393, p=0.009, f=0.664). Subthalamic DBS appears to have no substantial effect on vocal compensations, although it has been suggested that auditory-motor integration deficits contribute to higher vocal response magnitudes in pitch perturbation experiments with PD patients. Thus, DBS seems to be limited in modulating auditory-motor integration of speech in PD.